2004
DOI: 10.1103/physrevb.69.054108
|View full text |Cite
|
Sign up to set email alerts
|

Observation of wavelength shifts in ruby under shock compression to 36 GPa by time-resolved luminescence spectroscopy

Abstract: We have measured time-resolved luminescence spectra of ruby crystal subjected to impact-induced shock compression along the a axis to 36.3 GPa, recording the effect of shock and release waves on ruby R lines as streaks. Near the Hugoniot elastic limit ͑HEL͒, ruby luminescence lines blur, but above the HEL, blurring disappears and a clear image returns with the temporal behavior of luminescence lines differing from that in elastic region. Above the HEL, the luminescence intensity of shock-compressed ruby crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
1
10
1
Order By: Relevance
“…From the luminescence results, we can distinguish the two different types of behavior for our samples (Figure and Table ): samples A, B, and C exhibiting a stronger and sharper shifted R1 line accompanied by a negative shift, signifying the typical elastic region signal; samples D and E (containing IF-WS 2 ) having similarly very weak, broad, and short shifted R1 signal, evidencing the inelastic region characteristics . These results have confirmed that for samples D and E, the ruby crystal windows responded inelastically in the elastic region below the HEL of ruby.…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…From the luminescence results, we can distinguish the two different types of behavior for our samples (Figure and Table ): samples A, B, and C exhibiting a stronger and sharper shifted R1 line accompanied by a negative shift, signifying the typical elastic region signal; samples D and E (containing IF-WS 2 ) having similarly very weak, broad, and short shifted R1 signal, evidencing the inelastic region characteristics . These results have confirmed that for samples D and E, the ruby crystal windows responded inelastically in the elastic region below the HEL of ruby.…”
Section: Resultssupporting
confidence: 76%
“…However, the compression-shifted R1 signal for sample D (Figure f) was much weaker than that of sample B (Figure b), consistent with the more blurred signals in the streak image. Significantly, the intensity of the shifted R1 was much weaker, with only 32% intensity compared to that at ambient pressure (Figure d), and the very weak, broad, and short characteristics of such shifted R lines were indicative of an inelastic region signal . This is very surprising, as the shock pressure was below the HEL of ruby.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations